tert-Butoxide-Assisted Structural Transformation of 2-Aza-1,3,5-trienes: Fast Track to 5-Ethynyl-2-vinyl- and 2,5-Divinyl-1,3-thiazoles - Nedolya, Nina A.; Tarasova, Olga A.; Albanov, Alexander I.; Trofimov, Boris A. (Synthesis, 2018)
Treatment of 2-aza-1,3,5-trienes, methyl N-[2-alkoxy-1-(prop-2-ynylsulfanyl)buta-1,3-dienyl]- and methyl N-[1-(allylsulfanyl)-2-alkoxybuta-1,3-dienyl]iminoformates, which are easily obtained from lithiated alkoxyallenes, methoxymethyl isothiocyanate, and propargyl or allyl bromide, with t-BuOK or t-BuONa in DMSO–THF results in the formation of 5-ethynyl-2-vinyl- and 2,5-divinyl-1,3-thiazoles. The reactions are realized under mild conditions at ca. –30 °C for 30 minutes. An unprecedented structural transformation of the (prop-2-ynylsulfanyl)- and (allylsulfanyl)-substituted 2-aza-1,3,5-trienes into 1,3-thiazoles presumably occurs via α-deprotonation of the substituent at the sulfur atom (on the SCH2 group) followed by intramolecular [1,5]-cyclization at the imine group and aromatization (with elimination of MeOH).
Keywords: alkoxyallenes; methoxymethyl isothiocyanate; 2-aza-1,3,5-trienes; deprotonation; intramolecular cyclization; aromatization; 5-ethynyl-2-vinyl-1,3-thiazoles; 2,5-divinyl-1,3-thiazoles